Operator Theory, Analysis and Mathematical Physics - Janas, Jan; Kurasov, Pavel; Laptev, A.; Naboko, Sergei; Stolz, Günter (Operator Theory: Advances and Applications, 2007)
This volume contains lectures delivered by the participants of the international conference "Operator Theory, Analysis and Mathematical Physics" (OTAMP 2004), held at the Mathematical Research and Conference Center in Bedlewo near Poznan, Poland on July 6-11, 2004. The idea behind these lectures was to present interesting ramifications of operator methods in current research of mathematical physics. The main topics are functional models of non-selfadjoint operators, spectral properties of Dirac and Jacobi matrices, Dirichlet-to-Neumann techniques, Lyapunov exponents methods, and inverse spectral problems for quantum graphs. .